Rethinking the exchange rate disconnect puzzle theory in ASEAN-6 - Adhitya Wardhono; Badara Shofi Dana; M. Abd. Nasir (Economic Journal of Emerging Markets, 2017)
The theory of the exchange rate disconnect puzzle provides evidence of the instability of exchange rate relationship with macroeconomic fundamentals. This study will analyse the enactment of the theory of the exchange rate disconnect puzzle with the macroeconomic fundamental phenomenon in affecting the exchange rate movements in the ASEAN-6. The method of analysis Generalized Method of Moment (GMM) with panel data is used to provide an explanation for the existence of the theory of the exchange rate puzzle disconnect. Results the analysis showed the relationship between macroeconomic fundamentals through proxies of the monetary approach affect to exchange rate movements in the ASEAN-6.